English Sounds Produced by Sales And Marketing Staff at Sanur Paradise Plaza Hotel and Suites - Ni Made Tiara Krisnandi (Universitas Pendidikan Ganesha, 2012)
The aim of this study was to identify the English sounds produced by sales and marketing staff at Sanur Paradise Plaza Hotel and Suites. This study used descriptive design. The researcher observed and recorded the sounds pronounced by the staff by asking them to pronounce 39 different words. The sounds are taken from the International Phonetic Alphabetic. The English sounds produced by the staff were sixteen vowel sounds such as, [i], [ɜ], [i], [ə], [ɪ], [u], [u], [ӕ], [ʊ], [e], [ʌ], [ɑː], [ɒ], [o], [a] and [ɔ]; and twenty four consonant sounds such as, [p], [b], [t], [d], [k], [g], [ʧ], [ʤ], [f], [v], [θ], [ð], [s], [z], [ʃ], [ʒ], [h], [m], [n], [ƞ], [l], [r], [w] and [j]. In producing the sounds the staff were influenced by their first language and spelling of the words.